A theoretical and experimental study on laser-induced deterioration in wet grinding of Al2O3 engineering ceramic. Issue 9 (February 2016) - Zhang, X.; Deng, Z.; Chen, G.; Ren, Y.; Wan, L.; Liu, W.; Zhang, G.
Abstract A series of theoretical analyses and experimental investigations were performed to examine a strategy for laser-induced deterioration in wet grinding of Al2 O3 engineering ceramic. The mechanisms for laser-induced deterioration and wet grinding of the deterioration layer were theoretically analyzed, and the three key processing parameters that determined the micro-topography and distribution of the laser-inducing craters were proposed, including the laser power density, the laser spot overlap ratio, and the laser scanning track line overlap ratio. Further, the forming mechanism of the single pulse-inducing crater under different laser power densities and the interaction mechanisms between adjacent spots along the longitudinal and transverse directions were investigated. The optimal values of the key processing parameters were identified. To further evaluate the effect of laser-induced deterioration objectively, a comparative experiment was conducted under laser-induced deterioration wet grinding (LIDWG) and conventional grinding (CG) conditions. It was found that the procedure of laser-induced deterioration had a strong influence on the grinding results. The normal and tangential grinding forces for LIDWG condition were lower than those for CG condition, with a maximum reduction of 72.4 % (68.9 %).